A discourse analysis comparing Danish textbooks for nursing and medical students between 1870 and 1956 - Frederiksen, Kirsten (Nursing inquiry, 2010)
FREDERIKSEN K. Nursing Inquiry 2010; 17: 151–164 A discourse analysis comparing Danish textbooks for nursing and medical students between 1870 and 1956 Based on a discourse analysis inspired by the French philosopher Michel Foucault’s late work, the article compares Danish textbooks for nurses and doctors between 1870 and 1956. With the concept of a figure of thought, it is suggested that the discourses of knowledge addressed to nurses were constructed in a pattern in which intertwined arguments formed the figure of orderliness. These arguments were based on knowledge, the patient’s needs, the doctor’s needs and moral principles, including the needs of the profession and ethical–esthetic principles, whereas the pattern of the discourses of knowledge addressed to the doctor was based on knowledge of diseases reflecting a figure of scientific order. These patterns did not change throughout the period. In the textbooks for nurses, the nurse’s relation to self was an explicit subject, whereas the doctor’s relation to self was not part of the textbooks addressed to doctors. In light of Foucault’s late work, it is suggested that the discourses of knowledge contribute to maintaining the prevailing order in the society; it would be of interest to investigate whether the identified pattern has changed since 1956 and whether it has influenced other areas of nursing education and practice.